Organizational Culture, Organizational Commitment and Job Satisfaction: A Proposed Empirical-Based Human Resource Policy Framework - Maybelle Paulino; Rommel Yngson (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study proposes an empirical-based human resource (HR) policy framework that depicts the interactions among organizational culture, organizational commitment, and job satisfaction. The study’s framework is designed based on the previous literature. Drawing from the line-of-sight concept, this study posits that organizations’ HR policies should be grounded on the organization’s culture, organizational commitment, and employee’s job satisfaction. These factors help improve organizational performance and achieve the organization’s visions and objectives. This study proposes six hypotheses based on the conceptual framework outlined. The study also elucidates future research directions for management scholars. The findings of this study will benefit organizations’ executives, officers, administrators, human resource managers, and other policy- and decision-makers.